1987
DOI: 10.1111/j.1365-2621.1987.tb06697.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes of Vine‐Ripened Tomatoes within the Postharvest Handling System

Abstract: Quality characteristics of fresh-market tomatoes were monitored throughout the postharvest handlin g system to dcterminc the nature and extent ofcolor and firmness changes at component handling steps.Greatest changes in hue and chroma were observed during simulated warehouse ripening and storate (12.5"C). Greatest changes in color value (lightness) and firmness were noted during simulated retail ripening and storafc (21°C). Tomatoes harvested ;It carlier stages of maturity tended to maintain firmness longer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…The best models selected by the SAS STEPWISE Procedure were then reassessed with the SAS REG Procedure (SAS, 198.5) for final acceptance. The following equation developed by Shewfelt et al (1987) was used to calculate sensory equivalent scores for color.…”
Section: Methodsmentioning
confidence: 99%
“…The best models selected by the SAS STEPWISE Procedure were then reassessed with the SAS REG Procedure (SAS, 198.5) for final acceptance. The following equation developed by Shewfelt et al (1987) was used to calculate sensory equivalent scores for color.…”
Section: Methodsmentioning
confidence: 99%
“…The a*/b* value was calculated to measure the stage of red color, hue (h) to express tomato color changes (Shewfelt et al, 1987;Choi et al, 1995) and Chroma (C*) to analyze the color value of tomato.…”
Section: Color Quality Valuesmentioning
confidence: 99%
“…The stage of ripeness at harvest is considered a critical factor in postharvest quality of tomatoes (Kader et al 1977;Chung et al 1984;Shewfelt et al 1987;Stem et al 1994). Most supermarket tomatoes in the US.…”
Section: Introductionmentioning
confidence: 99%
“…are harvested at mature green or breaker stages to overcome long-distance transportation requirements (Kader et al 1977). Tomatoes harvested at earlier stages of maturity have shown to retain firmness longer through distribution and handling system (Shewfelt et al 1987), while sensory panels indicated early harvested and storage ripened tomatoes as less sweet, more sour, less tomato-like, and having more off-flavor than those picked at red-ripe stage (Kader et al 1977). Similarly, levels of total volatiles were found to be lower in tomatoes harvested at early stages of ripeness than those picked table ripe (Stem et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation